2007
DOI: 10.9755/ejfa.v12i1.5171
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the efficacy of black soap and kerosene mixture on the control of Pod sucking bugs (Clavigralla tomentosicollis stal.) on Cowpea (Vigna unguiculata (L.) Walp)

Abstract: Field experiment testing of various concentrations (2, 4, 6 and 8% vol/vol) of an aqueous black soap and kerosene as a control for pod damage by Clavigralla tomentosicollis Stal. indicated that the 8% concentration was the most effective in reducing pod injury and increasing the yield of seed in 'Dan-Sokoto' cowpeas. None of the treatments significantly reduced the abundance of the pod sucking insects on the plants. Application of 8% concentration should therefore be considered for recommendation as a control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…[44]. The insect can cause grain yield loss ranging from 20% -100% when left uncontrolled on susceptible crops especially during prolonged dry weather [46]. Cultural practices such as intercropping legumes including bambara groundnuts with cereals can reduce the bugs infestation [44].…”
Section: Pod Sucking Bugs (Clavigralla Tomentosicollis Stäl)mentioning
confidence: 99%
“…[44]. The insect can cause grain yield loss ranging from 20% -100% when left uncontrolled on susceptible crops especially during prolonged dry weather [46]. Cultural practices such as intercropping legumes including bambara groundnuts with cereals can reduce the bugs infestation [44].…”
Section: Pod Sucking Bugs (Clavigralla Tomentosicollis Stäl)mentioning
confidence: 99%
“…However, its high cost coupled with its potential hazards to the environment, humans, animals and livestock have necessitated the search for viable non chemical methods to reduce the consequences generally caused by pests. Pesticides not only cause environmental pollution especially by non-biodegradable, highly persistent residues, but they also off-set the dynamic equilibrium in aquatic ecosystem [14]. It also affect non target soil micro and macro fauna and flora, predatory beetles, spiders, birds, insect pollinators and other wild life.…”
Section: Introductionmentioning
confidence: 99%
“…Cultural control practices, pesticide applications and resistant crop varieties have in the past been used in the management of Clavigralla spp., but these were largely unsuccessful (Jackai & Adalla, 1997;Adipala, Nampala, Karungi, & Isubikalu, 2000;Koona, Osisanya, Jackai, Tamò, & Markham, 2002;Aliyu, Ladan, Ahmed, & Abdullahi, 2007). Several studies previously reported on the potential of egg parasitoids as biological control agents for pod sucking bugs eggs in Africa (Taylor, 1975;Asante, Jackai, & Tamò, 2000).…”
mentioning
confidence: 99%